Retailers of the Lviv region - Klapchuk, Viktoria A.; Lozynskyy, Roman M (Journal of the Belarusian State University. Geography and Geology, 2019)
We analyzed trading networks operating in the territory of the Lviv region. Also we determined the fraction of each retailers in the general structure of the retailers by region coverage. The research objects are 251 modern trade establishments, represented by such formats as minimarket, supermarket, hypermarket, discounters and cash & carry. The article analyzes the spatial development of the retail chains of Lviv as the largest city in the Lviv region. Determination of geospatial organization of the Lviv retailers allow us to identify perspective areas for the development of retailers. In the course of the research, it was found that one of the key indicators, in addition to the numbers of networks, is the general trading area of their establishments, after all it reflects the possibilities of the retailer’s in customer service. The largest areas, as a rule, have establishments in international trade networks, somewhat smaller – national networks, the smallest, respectively, in local area networks. For getting the complete information about the area of the trading establishments we used GIS methods. According to the received results, it was determined that the largest average area of retail establishments has international trade networks, and despite their small number, their fraction from the general is one of the largest. Using different indicators we created a database for cluster analysis, which makes possible to combine regions and cities of regional significance into certain groups according to the similarity of indicators. According to the results of the analysis, the districts of Lviv region were divided into 6 groups, and cities of regional significance for 4 groups. Received results can be used to determine the accessibility of the population to modern trade establishments, thus showing the level of development of social benefits, and also to create the investment attractiveness of some districts of the Lviv region.
Keywords: trading network; retailer; region coverage; universal retailers; minimarket; supermarket; hypermarket; «shop near the house»